2010
DOI: 10.1177/1469787410379683
|View full text |Cite
|
Sign up to set email alerts
|

A first year experience of student-directed peer-assisted learning

Abstract: This study aimed to evaluate the implementation of a same-year peer-assisted learning (PAL) scheme, introduced in the first year of an undergraduate degree. The students participated in voluntary timetabled PAL sessions which encouraged a cooperative approach through student-directed activities. An action research design was used, and evaluation at each stage led to subsequent modifications over three years of implementation. Evaluation showed that the majority of students agreed that PAL helped with social as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 16 publications
(10 reference statements)
5
84
0
1
Order By: Relevance
“…He adds that groups need to be given a sense of how much time is available for their work and that, at the end of it, all of them need to know what their peers have achieved. The advice to set clear instructions for group work to run smoothly was also supported by Hammond et al (2010) and Hillyard et al (2010) through their use of an explicit teaching concept: They suggest that individual instructors explain to students the purpose of using a particular group activity in their class. Altogether, some group rules may be established and group members' roles well defined in advance to mitigate possible internal disagreements among group members (Scott-Ladd & Chan, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…He adds that groups need to be given a sense of how much time is available for their work and that, at the end of it, all of them need to know what their peers have achieved. The advice to set clear instructions for group work to run smoothly was also supported by Hammond et al (2010) and Hillyard et al (2010) through their use of an explicit teaching concept: They suggest that individual instructors explain to students the purpose of using a particular group activity in their class. Altogether, some group rules may be established and group members' roles well defined in advance to mitigate possible internal disagreements among group members (Scott-Ladd & Chan, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Using PAL during the training of professional skills, the tutors and tutees should be senior students, [11,12,18] but PAL could also be implemented during the first year of study in physiotherapy. [14] One article conveyed the opinion that students from the same academic year could also assist. [12] Evidence is needed for occupational therapy, dietetics and nutrition, and optometry to determine at what level of their programmes PAL will be most beneficial.…”
Section: Pal In Allied Health Professions Programmesmentioning
confidence: 99%
“…[13][14][15][16][17][18] This indicated that knowledge on PAL in the allied health professions is limited.…”
Section: Pal In Allied Health Professions Programmesmentioning
confidence: 99%
See 2 more Smart Citations